DRUG-BASED THERAPIES FOR VASCULAR DISEASE IN MARFAN SYNDROME: FROM MOUSE MODELS TO HUMAN PATIENTS - Cook, Jason R. (2010)
Marfan syndrome is a congenital disorder of the connective tissue with a long history of clinical and basic science breakthroughs that have forged our understanding of vascular disease pathogenesis. The biomedical importance of Marfan syndrome was recently underscored by the discovery that the underlying genetic lesion impairs both tissue integrity and transforming growth factor-β regulation of cell behavior. This discovery has led to the successful implementation of the first pharmacological intervention in a connective tissue disorder otherwise incurable by either gene- or stem cell-based therapeutic strategies. More generally, information gathered from the study of Marfan syndrome pathogenesis has the potential to improve the clinical management of common acquired disorders of connective tissue degeneration.